A Listening Lesson Prototype for the First-Grade in Primary School - Triwidayati, Katarina Retno; Utami, Tresiana Sari Diah (Universitas Pendidikan Indonesia, 2019)
One of the main purposes of learning Bahasa Indonesia is to make students be fluent in using language. Language skills consist of two receptive skills (listening and reading), and two productive skills (speaking and writing). Those four skills are expected to be practiced equally. However, based on the previous research, listening lessons were rarely implemented in class. Moreover, listening lesson were inappropriately implemented by asking students to read. Additionally, the listening tests to measure the students’ listening proficiency were also unsuitable. Based on those findings, the researchers conducted a listening lesson developmental research for the first-grade primary school. This research is part of a developmental research referring to Gall, Gall, and Borg’s developmental research steps. This research is the second of five planned research phases. In this second phase, the researchers developed a listening lesson prototype validated by six validators. To validate the data, this research employed the triangulation method. Meanwhile, Miles and Huberman’s data analysis technique was utilized to analyze the data. The result of this research was a listening lesson prototype, including the mapping of basic competencies, networking of themes, determining of listening learning success indicators, learning stages, and listening evaluation.